Can intraparty democracy save party activism? Evidence from Korea. (January 2020) - Koo, Sejin
This article focuses on Korean parties to address the following gaps in the literature on party member activism: First, little attention has been paid to party members in non-Western democracies. Second, it is unclear how intraparty democracy is related to member activism. Unlike most industrialized democracies, South Korea has recently seen a notable growth in party membership. However, dues-paying remains the exception rather than the rule in the major parties, while the opposite is true for the minor, leftist parties. Using data from party member surveys, I examine the determinants of member activism across three Korean parties, focusing on the effect of members' evaluations of the internal democracy of their party. I argue that dues-paying has risen as a new form of activism as democracy has been consolidated, and present evidence for a paradox of intra-party democracy that members positively evaluating internal democracy of their party remain less active.